2014
DOI: 10.1186/1471-2393-14-157
|View full text |Cite
|
Sign up to set email alerts
|

WHO multicentre study for the development of growth standards from fetal life to childhood: the fetal component

Abstract: BackgroundIn 2006 WHO presented the infant and child growth charts suggested for universal application. However, major determinants for perinatal outcomes and postnatal growth are laid down during antenatal development. Accordingly, monitoring fetal growth in utero by ultrasonography is important both for clinical and scientific reasons. The currently used fetal growth references are derived mainly from North American and European population and may be inappropriate for international use, given possible varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 26 publications
0
31
0
1
Order By: Relevance
“…The present study is the fetal component of the WHO Multicentre Growth Reference Study, which aimed to establish growth charts for clinical use based on populations recruited from multiple countries [20]. …”
Section: Introductionmentioning
confidence: 99%
“…The present study is the fetal component of the WHO Multicentre Growth Reference Study, which aimed to establish growth charts for clinical use based on populations recruited from multiple countries [20]. …”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD) fetal growth studies 21 reported standards specific to four different ethnic-racial groups (non-Hispanic White, Hispanic, African American, and Asian) 21 , yet customization by factors other than race was not provided. Recently, a study sponsored by the World Health Organization (WHO) 20, 41 proposed a multi-ethnic growth standard customized only by fetal sex, despite the observation that other factors (e.g. country of origin, maternal age, height, and parity) had independent effects on EFW.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, they reflect the expected growth for each gestational age without the effects of prematurity. Their disadvantage is the sensitivity of ultrasonography to assess fetal weight, especially during the first weeks of gestation (15,21,22,23). The postnatal growth charts are longitudinal and constructed from sequential measurements of preterm infants, considering the delay of the early extrauterine growth (15).…”
Section: Preterm Growth Chartsmentioning
confidence: 99%